FAKTOR-FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING PADA PERUSAHAAN NON KEUANGAN - DIANA DIANA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2018)
This study aimed to analyze the factors that influence voluntary auditor switching in Indonesia. The independent variables used in this study are audit opinion, size of public accounting firm, change in management, profitability, financial distress, company growth and institutional ownership, and voluntary auditor switching as the dependent variable. The audited financial statements of non financial companies listed on the Indonesia Stock Exchange for the period 2014 to 2016 are used as secondary data in this study. The selection of samples used purposive sampling method and there are 78 companies and 234 observations meet those criteria for samples. This research is analyzed using logistic regression analysis to test the hypothesis. The result of this research show that independent variables namely audit opinion have influence on Audit Switching.While size of public accouting firm, change in management, financial distress, profitability percentage, institutional ownership, and company growth does not affect voluntary auditor switching.